PREVALENCE OF GERIATRIC DEPRESSION AND ASSOCIATED FACTORS AMONG ELDERLY PEOPLE IN FAMILY MEDICINE CLINIC - Yakar, Burkay; Olğun, Emel; Karakas, Selim; Önalan, Erhan; Pirincci, Edibe (Ankara Yildirim Beyazit University, 2021)
Objectives: Depression, which is an important public health problem and a determinant of disease burden, is one of the most common mental disorders, especially in the elderly population. The current study was aimed to investigate the prevalence of geriatric depression and associated factors among elderly people who admitted to the family medicine outpatient clinic. Materials and Methods: A total of 195 elderly participants aged 60 years have enrolled in this study. Demographic characteristics, medical history, psychosocial factors, and physical health status of individuals that may be associated with depression were obtained with a questionnaire. Depressive symptoms were assessed using the 30-item Geriatric Depression Scale (GDS). Results: Total of the 166 participants included in the study, 49.09% (n=81) had no depression, 4.24% (n=7) had probable depression, and 46.67% (n=77) had depression. Depression questionnaire scores of participants 75 years and over-aged were statistically higher than other age groups (p=0.001). Ability to make own daily work (OR: 19.78, Cl: 1.23-317.83, p=0.035), have a hearing problem (OR: 2.74, CI: 1:20 - 6:27 p=0.017) and fair sleep quality (OR: 10.62, Cl: 2.37-42.70, p=0.002) or poor sleep quality (OR: 4.24, Cl: 1.78-10.06, p=0.001) were independent risk factors that affecting the depression status. Conclusion: This study provides an alarming signal for health professionals and family physicians about the high prevalence of geriatric depression. We found that geriatric depression is associated with household income, education level, physical health, hearing problem, sleep status and history of falls in the elderly population. © 2021 Ankara Yildirim Beyazit University. All Rights Reserved.
AİLE HEKİMLİĞİ KLİNİĞİNDE YAŞLILARDA GERİATRİK DEPRESYON PREVALANSI VE İLİŞKİLİ FAKTÖRLER
Keywords: Elderly; Family practice; Geriatric depression